2014
DOI: 10.1186/1869-0238-5-2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating security and usability of profile based challenge questions authentication in online examinations

Abstract: Student authentication in online learning environments is an increasingly challenging issue due to the inherent absence of physical interaction with online users and potential security threats to online examinations. This study is part of ongoing research on student authentication in online examinations evaluating the potential benefits of using challenge questions. The authors developed a Profile Based Authentication Framework (PBAF), which utilises challenge questions for students' authentication in online e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
(39 reference statements)
0
22
0
2
Order By: Relevance
“…The usability analysis of text-based questions is not significantly different than other similar studies discussed in Table 1. While the effectiveness of text-based questions increased with improved question design from our previous study (Ullah et al 2014a), the issues contributing to incorrect answers such as syntactic variation, capitalization, incorrect spellings, memorability remained unchanged. In their study, Just and Aspinall (2009a) reported similar concerns for incorrect answers i.e.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…The usability analysis of text-based questions is not significantly different than other similar studies discussed in Table 1. While the effectiveness of text-based questions increased with improved question design from our previous study (Ullah et al 2014a), the issues contributing to incorrect answers such as syntactic variation, capitalization, incorrect spellings, memorability remained unchanged. In their study, Just and Aspinall (2009a) reported similar concerns for incorrect answers i.e.…”
Section: Discussionmentioning
confidence: 97%
“…We implemented an string-tostring comparison algorithm for authentication purposes (Schechter et al 2009;Ullah et al 2014a). Results in Table 4 show that, of the 890 text-based challenge questions randomly presented to students, 583 (66%) were answered correctly during the authentication process using an equality algorithm, which would increase to 74% if a more relaxed algorithm was implemented.…”
Section: Effectiveness Of Text-based Questionsmentioning
confidence: 99%
See 3 more Smart Citations